Gestational Trophoblastic Disease: Review of Cases Managed at B P Koirala Memorial Cancer Hospital - Pariyar, Jitendra; Shrestha, B; Shrestha, J; Shrestha, J; Rauniyar, BP; Regmi, SC (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: This study was done to analyze the clinical presentation and management outcomes of gestational trophoblastic disease managed at B.P. Koirala Memorial Cancer Hospital, Chitwan, Nepal. Methods: Descriptive study was conducted at B.P. Koirala Memorial Cancer Hospital. Case records of all gestational trophoblastic cases from January 2001 to December 2007 were analyzed regarding clinical details, investigations and treatment outcomes. Results: Forty-five cases of 16 to 50 years (mean 29.1 years) had gestational trophoblastic disease, among which 19 (43%) were of Tibeto- Burmese and 15 (33%) Indo-Aryan ethnic group. Hydatidiform mole, invasive mole and choriocarcinoma were observed in 17 (37.8%), six (13.3%) and 22 (48.8%) cases respectively. In seven cases (15.5%) molar pregnancy had occurred in primigravida, seven cases (15.5%) had previous molar pregnancy and in 16 (35.5%) cases GTD had occurred following abortion. Vaginal bleeding was the commonest presentation and 26 (57.8%) cases had anaemia. Eleven (24.5%) cases had theca luteal cyst, 17 (37.8%) had lung metastasis and 4 (8.9%) had brain metastasis. Chemotherapy was administered in 34 (75.5%) cases, among which 15 (33.3%) received single agent and 18 (40%) received multiagent chemotherapy. Hysterectomy was done in nine (20%) cases. Brain irradiation was done in a case with brain metastasis. Five (11.2%) cases with high WHO risk score left the hospital against medical advice. There were three (6.6%) mortalities. Thirty-seven (72.1%) cases were in remission and follow-up. Conclusions: Early diagnosis of disease and proper management strongly influences the outcome of GTD. Even in disseminated state GTD can be cured. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 1 / Issue 15 / Jan- June, 2013 / 18-21 DOI: http://dx.doi.org/10.3126/njog.v8i1.8855